Sexual rights in Uganda and the struggle for meaning in community. Issue 2 (3rd April 2017) - wa Tushabe, Tushabe
ABSTRACT: Drawing on lessons from the experiences of women who exchange same-sex erotic energies, this article suggests that advocates of same-sex human rights should take into account epistemic erasures colonized people experience when activism and policies regarding sexual freedom ignore various linguistic and community structures that create spaces for diverse ways of knowing and being . Since the late 1990s, the discourse on homosexuality in Uganda has motivated important debates concerning human values of sovereignty, rights, and family, and has expanded freedoms of sexual expression while at the same time conditioning these freedoms to be experienced in colonial ways of self-knowledge. The language that frames these debates continues to locate human rights for Ugandans who exchange same-sex erotic energies outside the locales—family, history, and language—of intelligible episteme for them. To make sense of this claim, I draw "exchange of same-sex erotic energies" from a saying in Rukiga language spoken by Bakiga in southwestern Uganda, okugira omukago mukika nikwokunywaana oruganda, to think about family and community in which same-sex erotic energies are lived and experienced. This article attempts to redirect attention from colonial constructions of homosexuality to indigenous and decolonial perspectives in relation to women in Uganda who exchange same-sex erotic energies in their struggle for meaning in community. I argue for pedagogies and epistemologies of place and memory in the struggle for human rights and sexual rights.